Posthuman Aesthetics : Perception and Relationality, Mapping the Field Through the Lens of Critical Posthumanism - Micali, Alberto; Pasqualini, Nicolò (Scenari, 2021)
Critical posthumanism offers the tools to overcome the epistemological limits of humanism. These are the limits of an epistemology of domination over otherness, particularly non-human alterities that, from the humanist standpoint, end up occupying an ancillary position with regard to the human-animal. As such, aesthetics needs to be rethought beyond these limits, rebutting an idea that matches with a transcendental notion of beauty, conceiving it as an ideal form. Rather, the viewpoint of critical posthumanism permits an alignment with a notion of aesthetics that pertains a field of relationality and perception. By drawing from these two axes, this article proposes a map of a posthuman aesthetics that aims to signal the ways in which matter becomes an intimate and active part of creative processes: a monstrous muse that, from a platonic inspiration for the human soul, becomes the carnal copula of an embodied mind. The ecological relation between human and non-human otherness is one of reciprocal contamination and co-determination: a relation in which art represents a faithful and heretical ostentation, a vibrant stratification. Moving from a mere creative and mono-directional process to a field of cosmological relationality and perceptive processuality, a posthuman aesthetics is, then, the becoming of such a plural contamination, allowing different forms of individuation and processes of subjectivation.